Training of Trainer Kasipang (Psychoeducation of Pro-Environmental Behavior) on Guidance and Counseling Teachers in Banjar Regency - Rika Vira Zwagery; Neka Erlyani; Rahmi Fauzia; Marina Dwi Mayangsari (Lambung Mangkurat, 2023)
One way to overcome and prevent that can be done to increase student awareness and shape pro-environmental behavior is through the learning process with psychoeducational methods. Psychoeducation is not carried out directly to students, but is taught to teachers through the